Free Scholarly Electronic Journals: How Good Are They? - Michael Fosmire; Song Yu (Issues in Science and Technology Librarianship)
Amidst the furor of serials price increases, there is a steadily growing segment of the serials landscape with prices that can't be beat, that is to say, free. Many scholarly journals are freely available in electronic format (no subscription fee or membership required), but there has been little assessment of their impact on scholarly research. A fairly comprehensive list of free scholarly electronic journals in the science, technology, and medical fields was compiled and was examined using citation analyses. The results indicate that, unlike the situation five years ago (Harter 1998), there are several free scholarly electronic journals that have a significant impact on their respective fields.